Truncated and Spheroidal Ag Nanoparticles: A Matter of Size Transformation - Nurul Akmal, Che Lah; Mohd Rafie, Johan; Samykano, Mahendran; Mohd Mawardi, Saari (Springer Berlin Heidelberg, 2017)
The ordered arrays of anisotropic mesostructure metal nanoparticle (diameter size in the range of 15 to 200 nm) characteristics are indeed influenced by the combined effect of packing constraints and inter-particle interactions, that is, the two morphological factors that strongly influence the creation of the particles’ shape. In this work, we studied on how the degree of truncation of Ag nanoparticles authorised the mesostructured morphologies and particle orientation preferences within the mesosparticle arrays. The Ag represented the best and most versatile candidate and known for its highest electrical conductivities among other transition metals in periodic table. The interest is motivated by the need to understand the inevitable morphological transformation from mesoscopic to microscopic states evolve within the scope of progressive aggregation of atomic constituents of Ag system. The grazing information obtained from HR-TEM shows that Ag mesosparticles of highly truncated flake are assembled in fcc-type mesostructure, similar to the arrays formed by microscopic quasi-spherical structure, but with significantly reduced packing density and different growth orientations. The detailed information on the size and microstructure transformation have been gathered by fast Fourier transform (FFT) of HR-TEM images, allowing us to figure out the role of Ag defects that anchored the variation in crystallite growth of different mean diameter size particles. The influences on the details of the nanostructures have to be deeply understood to promote practical applications for such outstanding Ag material.